Evaluating the potential of graphene oxide to promote skeletal muscle complex regeneration - Yulu Chen; Zeyu Zhu; Yian Shen; Xuling Liu; Yushi He; Chengqi Lyu; Jiayu Lu (Frontiers in Bioengineering and Biotechnology)
BackgroundRepair and regeneration of the musculoskeletal system are critical for maintaining mobility, physical function, and overall quality of life. This study aimed to optimize the size and concentration of graphene oxide (GO) to achieve a balance that enhances the proliferation and myogenic differentiation of C2C12 cells and investigate the underlying mechanisms, including the activation of key myogenic genes and signaling pathways. Additionally, the effects of exosomes derived from GO-treated C2C12 myoblasts on osteoblasts were explored.MethodsC2C12 cells were cultured with different concentrations (0.1, 0.5, 2.5, 12.5, and 62.5 μg/mL) and particle sizes (>500 and <500 nm) of GO. Thereafter, cell viability, proliferation, cycle, and migration were evaluated via fluorescence staining, CCK-8, flow cytometry, and scratch assays, respectively. Immunofluorescence, polymerase chain reaction, and RNA sequencing (RNA-seq) were used to detect the effects of GO on C2C12 cell differentiation and explore the related molecular mechanisms. Furthermore, RNA-seq analysis was performed to investigate the impact of exosomes derived from GO-treated C2C12 myoblasts on MC3T3-E1 cells.ResultsGO with particle sizes of >500 nm at a concentration of 2.5 μg/mL significantly enhanced C2C12 cell proliferation and myogenic differentiation. Increased GO conductivity played a crucial role in supporting MyoD expression and promoting myocyte differentiation, likely by modulating membrane electrical activity and facilitating intercellular signaling. These effects were associated with the activation of the PI3K-Akt signaling pathway and the upregulation of the NFATc1 gene, further highlighting the role of GO’s conductive properties in regulating myogenic differentiation. Exosomes derived from GO-treated myoblasts upregulated genes such as PDGFRB, COL12A1, and TBX2 while downregulating inflammation-related genes such as C3, thereby demonstrating the crosstalk between muscle and bone cells.ConclusionThe conductive properties and surface roughness of GO significantly enhanced interactions between muscle and bone tissues, consequently facilitating effective musculoskeletal repair. This study suggests that GO can serve as a promising material for integrated approaches in musculoskeletal tissue engineering by promoting both myogenic differentiation and osteoblastic activity. Our findings highlight the potential utility of GO in regenerative medicine, offering a novel strategy for musculoskeletal regeneration.